TINJAUAN YURIDIS TINDAK PIDANA PENYEBARAN KEBENCIAN MELALUI MEDIA ELEKTRONIK MENURUT UNDANG-UNDANG NOMOR 19 TAHUN 2016 TENTANG INFORMASI DAN TRANSAKSI ELEKTRONIK (STUDI KASUS PUTUSAN NOMOR: 572/PID.B/2016/PN.JKT.SEL) - Parlin Dony Sipayung (LP2MTBM MAKARIOZ, 2018)
Information and Transactions electronics has changed the behavior of people and human civilization globally. In addition, the development of information and electronic transactions has caused significant social change to take place so quickly. Electronic information and transactions currently have a positive impact on their development as well as in trade transactions, banking, access to various types of information such as economics, business, education, entertainment, sports, politics and others. The development of electronic media or the so-called internet is increasingly sophisticated and rapidly increasing. The emergence of social media such as Facebook, Twitter, Instagram, Path, Whatssup, Line and added use of Smartphones and / or Gadgets adds to the author's belief that the current of globalization is unavoidable. The internet as information and electronic transactions have positive and negative effects. On the positive side, the internet functions to find information, games, entertainment facilities, business activities such as E-Commerce and other activities that are online. But from the negative side, this online business activity can be used as a crime such as fraud, the spread of false news through social media, the spread of hatred, wiretapping, hacking (hack) through the internet network and so on.The research method used normative juridical research method with primary legal material, namely the Law on Information and Electronic Transactions Number 19 of 2016 concerning Amendment to the Law on Information and Electronic Transactions Number 11 of 2008, secondary legal material consisting of scientific books, and tertiary legal material in the form of a legal dictionary and Indonesian dictionary.In this study the measure of freedom of opinion with the spread of hatred where freedom can be a right of every person to convey an opinion that is in his mind or heart, but because of the delivery that contains provocation, incitement, or insult to another individual or group then that is what is called the spread of hatred and in the imposition of sanctions on the crime of spreading hatred through electronic media that was dropped on Defendant Feriyanto by the South Jakarta District Court, the Panel of Judges in the decision Number: 572 / Pid.B / 2016 / PN.Jkt.Sel. , impose imprisonment sanctions for 1 (one) year 6 (six) months and a fine of Rp.100,000,000 (one hundred million rupiah), subsidized 4 (four) months. This sentence is lighter than the demands of the Public Prosecutor who demanded 2 (two) years 6 (six) months and a fine of Rp.100,000,000 (one hundred million rupiah), subsidized 4 (four) months of imprisonment. This decision was made because the judge's judgment included, for example, the Defendant had never committed a crime, the defendant had a living life to provide for his wife and child and the defendant promised not to repeat his actions. So with this incident there should be socialization and / or counseling about the spread of hatred through social media and its legal consequences so that people are careful and prudent when using social networks.